The association between vitamin K and medial tibial-femoral knee osteoarthritis progression: Data from the osteoarthritis initiative. Issue 3 (September 2021) - Horace, Reuben William; Roberts, Mary; Lu, Bing; Driban, Jeffrey B.; McAlindon, Timothy; Eaton, Charles B.
Abstract: Objective: We sought to examine the prospective association of vitamin K with radiographic progression of knee osteoarthritis. Methods: In OAI, 1977 participants with radiographic knee OA and having dietary data at baseline were followed up to 12, 24, 36 and 48 months. Vitamin K was assessed with a Block Brief Food Frequency Questionnaire completed at baseline. To evaluate knee OA progression, we used quantitative medial tibiofemoral joint space width (JSW) based on plain radiographs. Progression was defined by measured Joints Space Width (JSW). The generalized linear mixed model was used to test the association of vitamin K and change in JSW over time, while adjusting for baseline KL grade and other potential confounding factors. Results: We found a relationship between dietary Vitamin K with structural progression of knee osteoarthritis measured by quantitative JSW in a dose response manner. When stratified among KL groups, a significant trend was seen in the KL2 (p ​< ​0.025) Conclusion: Our results suggest that decreased vitamin K intake from food may be associated with increased progression of knee OA. Replication of these findings in other studies validating decreased vitamin K intake leading to increased knee OA progression are needed. Significance: This study provides insight into a potential novel risk factor for the progression of knee OA. These findings have may have clinical implications given the potential for Vitamin K to be a simple therapy for knee OA.